Nanoindentation response of 3D printed PEGDA hydrogels in hydrated environment - Hakim Khalili, Mohammad; Williams, Craig J.; Micallef, Christian; Duarte Martinez, Fabian; Afsar, Ashfaq; Zhang, Rujing; Wilson, Sandra; Dossi, Eleftheria; Impey, Susan A.; Goel, Saurav; Aria, Adrianus Indrat (American Chemical Society, 2023)
Hydrogels are commonly used materials in tissue engineering and organ-on-chip devices. This study investigated the nanomechanical properties of monolithic and multilayered poly(ethylene glycol) diacrylate (PEGDA) hydrogels manufactured using bulk polymerization and layer-by-layer projection lithography processes, respectively. An increase in the number of layers (or reduction in layer thickness) from 1 to 8 and further to 60 results in a reduction in the elastic modulus from 5.53 to 1.69 and further to 0.67 MPa, respectively. It was found that a decrease in the number of layers induces a lower creep index (CIT) in three-dimensional (3D) printed PEGDA hydrogels. This reduction is attributed to mesoscale imperfections that appear as pockets of voids at the interfaces of the multilayered hydrogels attributed to localized regions of unreacted prepolymers, resulting in variations in defect density in the samples examined. An increase in the degree of cross-linking introduced by a higher dosage of ultraviolet (UV) exposure leads to a higher elastic modulus. This implies that the elastic modulus and creep behavior of hydrogels are governed and influenced by the degree of cross-linking and defect density of the layers and interfaces. These findings can guide an optimal manufacturing pathway to obtain the desirable nanomechanical properties in 3D printed PEGDA hydrogels, critical for the performance of living cells and tissues, which can be engineered through control of the fabrication parameters.
Keywords: poly(ethylene glycol) diacrylate; nanoindentation; 3D printing; cross-linked hydrogels; creep behavior